Local Interferences: Mapping the City as Resonant ‘Counter-Text’ - M. Boenisch, Peter (Peripeti, 2022)
Building on D.J. Hopkins’s ‘counter-textual dramaturgy’ and using as principal example the curatorial strategy of the 2018 Palermo edition of the arts biennial Manifesta, both of which introduced urban study research strategies proposed by Dutch architect Rem Koolhaas, this essay discusses the strategy of dramaturgic mapping as a way of generating ‘resonant interference’, as I call it drawing on a concept by German sociologist Hartmut Rosa. I argue that mapping fosters attention for common, resonant micro-narratives whose productive interferences help to dramaturgically embed art works within contemporary plural and diverse local cultural contexts.